Does political pressure matter in bank lending? Evidence from China. Issue 5 (9th November 2017) - Cai, Weixing; Xu, Fangming; Zeng, Cheng
Abstract: Using provincial data from China between 2002 and 2011, we find substantial evidence indicating a positive association between the growth of bank loans issued by commercial banks and the political pressures faced by provincial leaders. This association is particularly true for state‐owned banks, which are much more politically pressurized than others, but is relatively attenuated in provinces with a more developed banking sector. We also find that bank loans issued under greater political pressures are less commercially oriented and have lower quality. Our findings are robust to a variety of sensitivity analyses and alternative measures of political pressure. Overall, our study contribute to a growing literature emphasizing the role of the political incentives of government officials in fuelling economic growth through credit allocation.